1997
DOI: 10.1016/s0370-2693(96)01492-x
|View full text |Cite
|
Sign up to set email alerts
|

Monopole configuration in Weinberg-Salam model

Abstract: We present a new type of spherically symmetric monopole and dyon solutions with the magnetic charge 4π/e in the standard Weinberg-Salam model. The monopole (and dyon) could be interpreted as a non-trivial hybrid between the abelian Dirac monopole and non-abelian 't Hooft-Polyakov monopole (with an electric charge). We discuss the possible physical implications of the electroweak dyon.Typeset using REVT E X 1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
297
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(306 citation statements)
references
References 18 publications
8
297
1
Order By: Relevance
“…More recently, it has been proposed [5] that solutions yielding MMs could arise within the electroweak theory itself. This Cho-Maison, or electroweak MM, would be expected to have a mass of the order of several TeV.…”
Section: Jhep07(2017)054mentioning
confidence: 99%
“…More recently, it has been proposed [5] that solutions yielding MMs could arise within the electroweak theory itself. This Cho-Maison, or electroweak MM, would be expected to have a mass of the order of several TeV.…”
Section: Jhep07(2017)054mentioning
confidence: 99%
“…Obviously the existence of the monopole solution assures that the standard model has the monopole [5,6,20]. If so, the remaining question is if this monopole is optional or not.…”
Section: Electroweak Monopole: a Reviewmentioning
confidence: 99%
“…After the Dirac monopole we have had the Wu-Yang monopole [2], the 't Hooft-Polyakov monopole [3], the grand unification (Dokos-Tomaras) monopole [4], and the electroweak (Cho-Maison) monopole [5,6]. But only the electroweak monopole become realistic enough to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…'t Hooft and Polyakov, in 1974, independently demonstrated that a Grand Unified Theory (GUT) scheme possesses a monopole solution when a U(1) subgroup of electromagnetism that is embedded into a larger gauge group is spontaneously broken by the Higgs mechanism [2,3]. Monopole solutions have been proposed to arise within the electroweak theory itself [4], which relies on spontaneous gauge symmetry breaking. The Cho-Maison electroweak monopole would have a mass of the order of several TeV [5,6] and is possibly within the range of the Large Hadron Collider (LHC).…”
Section: Introductionmentioning
confidence: 99%
“…The minimum value of the quantisation number n varies between different theories. According to Dirac, n = 1, 2, 3.., while according to Schwinger, as well as, Cho and Maison, n = 2, 4, 6.. [4,7], and n = 3, 6, 9.. or n = 6, 12, 18.. if one considers the elementary charge to be carried by the down quark. As a result of the high value of the Dirac magnetic charge, a high velocity monopole is expected to suffer energy losses in matter over ≈4700 times higher than a muon [8][9][10].…”
Section: Introductionmentioning
confidence: 99%